Emerging neurotrophic role of GABAB receptors in neuronal circuit development - Gaiarsa, Jean-Luc; Porcher, Christophe (Frontiers in Cellular Neuroscience, 2013)
The proper development of highly organized structures in the central nervous system is a complex process during which key events – neurogenesis, migration, growth, differentiation and synaptogenesis – have to take place in an appropriate manner to create functional neuronal networks. It is now well established that GABA, the main inhibitory neurotransmitter in the mammalian brain, plays more than a classical inhibitory role and can function as an important developmental signal early in life. GABA binds to chloride-permeable ionotropic GABAA receptors and to G-protein-coupled GABAB receptors. Although most of the trophic actions of GABA have been attributed to the activation of GABAA receptors, recent advances show that GABAB receptors also regulate fundamental steps of network development. This review summarizes some of the recent progress about the neurotrophic role of GABAB receptors to neuronal development.